Revaccination of Children after Completion of Standard Chemotherapy for Acute Leukemia - Patel, Soonie R.; Ortín, Miguel; Cohen, Bernard J.; Borrow, Ray; Irving, Diane; Sheldon, Joanne; Heath, Paul T. (Clinical infectious diseases, 2007)
Background. After the treatment of patients with acute leukemia, there is a decrease in vaccine-specific antibody and an increased susceptibility to certain vaccine-preventable diseases. A simple revaccination schedule is warranted. Method. Fifty-nine children (age, 1–18 years) who had completed standard chemotherapy in accordance with Medical Research Council of United Kingdom protocols were recruited. All children received a single dose of Haemophilus influenzae type b (Hib), tetanus, diphtheria, acellular pertussis, meningococcus C, polio, measles, mumps, and rubella vaccines ⩾6 months after completion of treatment. Antibody concentrations were measured before vaccination and 2–4 weeks and 12 months after vaccination. Results. Prevaccination antibody levels were protective for all patients for tetanus (geometric mean concentration [GMC], 0.13 IU/mL; 95% CI, 0.1–0.17 IU/mL), for 87% for Hib (GMC, 0.5 µg/mL; 95% CI, 0.37–0.74 µg/mL), for 71% for measles (GMC, 301 mIU/mL; 95% CI, 163–557 mIU/mL), for 12% for meningococcus C (geometric mean titer [GMT], 1 : 2.9; 95% CI, 1 : 2.2 to 1 : 3.9), and for 11% for all 3 poliovirus serotypes. Revaccination resulted in a significant increase in levels of antibody to each vaccine antigen, with 100% of patients achieving optimal antitetanus antibody concentrations (defined as >0.1 IU/mL; 1.5 IU/mL; 95% CI, 1.1–2.1 IU/mL), 93% achieving optimal antibody concentrations to Hib (defined as >1.0 µg/mL; 6.5µg/mL; 95% CI, 5.1–8.2 µg/mL), 94% achieving optimal antibody concentrations to measles (defined as ⩾120 mIU/mL; 2720 mIU/mL; 95% CI, 1423–5198 mIU/mL), 96% achieving optimal antibody concentrations to meningococcus C (defined as ⩾1 : 8; 1 : 1000; 95% CI, 1 : 483–1 : 2064), and 85% achieving optimal antibody concentrations to all the 3 poliovirus serotypes (defined as ⩾1 : 8). For the majority of subjects, protection persisted for at least 12 months after vaccination. Conclusion. Revaccination of children after standard chemotherapy is important, and protection can be achieved in the majority of these children using a simple schedule of 1 vaccine dose at 6 months after completion of leukemia therapy.